MODIFIKASI MESIN PENGUPAS KULIT KOPI KAPASITAS 241 KG/JAM - Sir Anderson (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2022)
Processing of coffee skin peelers generally still uses manual or semi-mechanical peelers and to overcome this, a mechanical coffee peeler driven by a gasoline motor is needed. The purpose of modifying this coffee skin peeler machine is to find the perfect tools that have been made previously. This machine modification is expected to help the process of peeling the coffee skin so that it can improve the quality of the coffee. The implementation method for modifying the coffee peeler machine starts with the plan, preparing the construction materials for machines, gasoline motors, gears and chains, peeling rollers, push rollers, iron plates and elbow plates. The next stage is assembling the machine and the engine position. The process ends with testing the tool, data analysis, and concluding the results of the tool. The result of specification this modified coffee peeler machine is capable to peel the coffee skin until 241.2kg/hour. The engine dimensions are 74 mm x 31 mm x 105 mm, using a gasoline motor of 1 hp 2800 rpm, the frame uses an elbow profile of 30 x 30 x 3 mm, the transmission system uses 2 pulleys D = 75 mm and 200 mm connected to a type A v-belt -54.